Faktor-Faktor Penentu Penerapaan Konservatisme Akuntansi Pada Perusahaan Non Manufaktur - Astutik, Indah Dwi; Wulandari, Anis (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2025)
The purpose of this study is to ascertain how Accounting Conservatism is impacted by Financial Distress, Profitability, Leverage, and Company Size. This kind of research is quantitative, and SPPS software version 25 is used as a statistical tool for analysis. The non-manufacturing businesses listed on the Indonesia Stock Exchange for the 2021–2022 period were the subject of this study. Purposive sampling is the procedure used in the sample gathering process. Multiple regression models, classical assumption tests, descriptive statistics, and hypothesis testing are the analysis approaches employed. The study's findings suggest that accounting conservatism is influenced by profitability. Meanwhile, Accounting Conservatism is unaffected by Financial Distress, Leverage, and Company Size.